Searching for anti-hyperglycemic phytomolecules of Tecoma stans - Taher, Mohamed Abdel-Hamid; Dawood, Dawood Hosni; Sanad, Mostafa Ibrahim; Hassan, Ramadan Ahmed (European Journal of Chemistry, 2016)
Tecoma stans plant is well postulated to decrease blood glucose level, but its mode of action and the molecules responsible are still controversial. Thus, the aim of this study was to evaluate the effect of leaves methanol extract of Tecoma stans and some of its fractions on starch tolerance in healthy rats, in vitro inhibition of α-amylase, and their effects of sub-chronic administration of glucose, lipid pattern, kidney and liver functions and antioxidant status in streptozotocin (STZ) induced diabetic rats. In starch tolerance experiment, both ethyl acetate and crude flavonoids fractions decreased glycemic peak values in healthy rats to extent similar to that of acarbose. In STZ sub-chronic experiment all preparations of Tecoma stans significantly decreased fasting glucose with variable degrees. The results indicated that the crude methanol extract had the most antidiabetic potential followed by the methylene chloride rich alkaloid fraction while the crude flavonoids fraction achieved the lowest effect. All Tecoma stans different preparations have positive effects on serum lipid pattern, kidney and liver function parameters, in addition to the antioxidant parameters (MDA and GSH) in liver tissues. In conclusion, the present study suggested that the alkaloids synergistically act as antidiabetic agent with other bioactive compounds of Tecoma stans especially flavonoids as hypoglycemic agents and the ethyl acetate fraction had the most powerful effects.